2017
DOI: 10.1016/j.celrep.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock Regulates Adipogenesis by a Per3 Crosstalk Pathway to Klf15

Abstract: Summary The generation of new adipocytes from precursor cells (adipogenesis) has implications for systemic metabolism and is a commonly used model for studying the process of cell differentiation in vitro. Previous studies from us, and others, suggested that the peripheral circadian clock can influence adipogenesis in vitro, but the mechanisms driving this activity and the relevance for adipogenesis in vivo are unknown. Here we reveal that mouse adipocyte precursor cells (APCs) contain a circadian clock that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 45 publications
(54 reference statements)
5
63
0
Order By: Relevance
“…Regarding single Per1 and Per2 mutants, although fertile, they exhibit lower reproductive success than the control group, as occurs in aged wild-type (WT) mice. The role of Per3 in regulating metabolism and adiposity has also been described in animal studies [74,75]. Per1 and Per2 mutations cause advanced aging [76].…”
Section: Per1 1 2 Andmentioning
confidence: 86%
“…Regarding single Per1 and Per2 mutants, although fertile, they exhibit lower reproductive success than the control group, as occurs in aged wild-type (WT) mice. The role of Per3 in regulating metabolism and adiposity has also been described in animal studies [74,75]. Per1 and Per2 mutations cause advanced aging [76].…”
Section: Per1 1 2 Andmentioning
confidence: 86%
“…27 These studies demonstrated that primary APCs contain a circadian clock. 23 However, to our surprise, our further investigations elucidated that expression of the classic core clock component Per1 does not significantly oscillate in APCs. 23 Strikingly, we discovered that Per3, has the most robust circadian expression profile of the Per paralogs in primary APCs.…”
Section: Resultsmentioning
confidence: 75%
“…23 However, to our surprise, our further investigations elucidated that expression of the classic core clock component Per1 does not significantly oscillate in APCs. 23 Strikingly, we discovered that Per3, has the most robust circadian expression profile of the Per paralogs in primary APCs. 23 These findings suggested to us that Per3 might have a particularly prominent role in the context of APC biology.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations